LANGUAGE CHOICE AND PERCEPTION OF EFL LEARNERSâ€™ COMPLIANCE TOWARDS STAY AT HOME HEALTH PROTOCOL DURING COVID-19 PANDEMIC - Adip Arifin (PROJECT (Professional Journal of English Education), 2023)
During the COVID-19 outbreak, Indonesian government continuously announces its people for strictly obeying health protocols; one of them is to keep â€œStay at home.â€ The announcement was given in spoken and written form through various media, such as national TV broadcasts, social media, online newspaper, and government official websites. This study is aimed at investigating the language choice realized in government appeals for letting Indonesian EFL students â€œStay at home.â€ A total of 389 respondents were involved, varied from diploma to postgraduate degree (from first to above four year) who were chosen purposively based on the basis of their availability, residence, and convenience. The data were collected through online questionnaire which piloted first and examined its reliability through SPSS (0.88 Cronbachâ€™s Alpha).Â  The data then analyzed quantitatively by employing descriptive statistics; particularly finding their frequency distribution. The result of analysis showed that the use of inspirative language was the most liked option, chosen by 341 respondents (185 agree and 156 strongly disagree). Other language choices preferred were figurative (336 positive responses), solutive (331 positive responses) and persuasive (329 positive responses). In contrast, the language choices which showed higher negative response were Interrogative (50 responses), permissive (26 responses), exclamative (24 responses), and imperative (20 responses). The findings suggested that the use of effective language choice affects much on respondentsâ€™ compliance to obey COVID-19 health protocol, particularly for stay at home.Â Keywords:Â  Language Choice; Government Appeal; Health Protocols; Indonesian EFL learners